Challenges of implementing the green building concept in Mosques - Sahid, Sahid; Sunartio, Anindhita Nugroho; Lukman, Aldyfra Luhulima; Wirakusumah, Indri Astrina Indrarani; Ramadhan, Adam; Lazuardi, Klarissa; Angeline, Cheryl (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The Republic of Indonesia's Ministry of Religion reports more than 700,000 mosques in the country. Insufficient research has been conducted concerning this mosque-turned-building, particularly regarding how it may help the country accomplish its environmental commitments. The Istiqlal mosque received a green building assessment certificate (Excellence in Design for Greater Efficiency) from the International Finance Corporation in April 2022. This certificate should serve as a foundation for future research into the distinctive features of mosque building designs in Indonesia and their potential to contribute to accomplishing national environmental targets. Mosque buildings as an embodiment of the concept of Rahmatan Lil Alamin or mercy for all of nature should be in line with the concept of green buildings which strive to preserve nature. This research aims to determine the challenges of implementing the green building concept in mosque buildings with a case study of two mosques in the city of Bandung. To identify their traits, this study employed observational methods, case studies, and interviews with mosque managers. The Minister of Public Works Regulation Number 21 of 2021 about Green Building Performance Assessment will be employed to examine and assess the gathered data. The outcomes demonstrate that the low-performance value persists. Considerable work is required to achieve the desired results. In-depth talks with stakeholders are also required to map the distinctive qualities of mosque structures and identify methods in which they can support the realization of national environmental preservation objectives while also exemplifying the principles of Rahmatan lil Alamin.